MiR-128-3p Alleviates Spinal Cord Ischemia/Reperfusion Injury Associated Neuroinflammation and Cellular Apoptosis via SP1 Suppression in Rat - Wang, Dan; Chen, Fengshou; Fang, Bo; Zhang, Zaili; Dong, Yan; Tong, Xiangyi; Ma, Hong (Frontiers in Neuroscience, 2020)
Background: Neuroinflammation and cellular apoptosis caused by spinal cord ischemia/reperfusion (I/R) injury result in neurological dysfunction. MicroRNAs (miRs) have crucial functions in spinal cord I/R injury pathogenesis according to previous evidences. Herein, whether miR-128-3p contributes to spinal cord I/R injury by regulating specificity protein 1 (SP1) was assessed. Methods: A rat model of spinal cord I/R injury was established by occluding the aortic arch for 14 minutes. Then, miR-128-3p’s interaction with SP1 was detected by dual-luciferase reporter assays. Next, miR-128-3p mimic and inhibitor, as well as adenovirus-delivered shRNA specific for SP1 were injected intrathecally for assessing the effects of miR-128-3p and SP1 on rats with spinal cord I/R injury. SP1, Bax and Bcl-2 expression levels in I/R injured spinal cord tissues were evaluated by Western blotting, while IL-1β, TNF-α and IL-6 were quantitated by ELISA. Tarlov scores were obtained to detect hind-limb motor function. Evans blue (EB) dye extravasation was utilized to examine blood-spinal cord barrier (BSCB) permeability. Terminal deoxynucleotidyl transferase mediated dUTP nick end labeling (TUNEL) staining was performed for neuronal apoptosis assessment. Results: MiR-128-3p expression was decreased, while SP1 amounts were increased in rat spinal cord tissue specimens following I/R. SP1 was identified as a miR-128-3p target, and downregulated by miR-128-3p. MiR-128-3p overexpression or SP1 silencing alleviated I/R-induced neuroinflammation and cell apoptosis, and improved Tarlov scores, whereas pretreatment with miR-128-3p inhibitor aggravated the above injuries. Conclusions: Overexpression of miR-128-3p protects neurons from neuroinflammation and apoptosis during spinal cord I/R injury partially by downregulating SP1.